UJI AKTIVITAS ANTIOKSIDAN BUAH CABAI KATOKKON (Capsicum chinense Jacq.) ASAL TANA TORAJA DENGAN METODE DPPH - Taufiq Taufiq; Rusmin Rusmin; Arief Azis (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Chili pepper (Capsicum sp.) known to contain vitamin C which can act as a source of antioxidants. The purpose of this study was to determine the amount of antioxidant activity of ethanol extract of chili katokkon (Capsicum chinense Jacq.) and Vitamin C. The extraction method used is maceration. Antioxidant activity was determined using the DPPH method, which then measured the absorbance using a UV-Vis spectrophotometer and then repeated up to three times. The value of IC50 chili katokkon in replication 1 is 51.2678 µg/mL, replication 2 is 51.2275 µg/mL, and replication 3 is 50.2991 µg/mL, so that the average value of IC50 chili katokkon is 50.9315 Keywords : Katokkon Chili, antioxidant, IC50 value. while the IC50 value of vitamin C in replication 1 is 6.1926 µg/mL, replication 2 is 6.3202 µg/mL, and replication 3 is 6.2253 µg/mL, so that the average value of IC50 vitamin C is 6.24603 µg/mL. based on these results, it was concluded that the level of antioxidant power of katokkon chili is at a strong level (50-100 µg/mL) while vitamin C is at a very strong level (50 µg/mL).